Laboratory Evaluation of the Effectiveness of Paraffin Oil and Insecticide Combination Based on Spinetoram and Permethrin to Control Weaver Ant (Oecophylla smaragdina Fabricius) - Habriantono, Bakhroini; Masnilah, Rachmi; Kustiawan Alfarisy, Fariz (Jurnal Ilmiah Inovasi, 2025)
Paraffin oil is known to be effective as a pest control agent. It is more toxic to pest insects while being safer for plants, humans, and beneficial organisms that act as natural enemies. Paraffin oil is also known for its ability to be mixed with various other pesticides, which can extend its effectiveness. This capability is particularly useful for reducing insecticide dosages in the field. This study aims to determine the best treatment combination of paraffin oil with insecticides containing the active ingredients spinetoram and permethrin on weaver ants (Oecophylla smaragdina), which in certain cases can become pests in laboratory settings. The findings of this study can potentially be used to minimize insecticide usage. The application of paraffin oil and its combinations with spinetoram and permethrin insecticides was carried out using a topical or direct spraying method on weaver ants. The study was designed using a Completely Randomized Design (CRD) with one factor, varying combinations of paraffin oil with spinetoram and permethrin insecticides. The observed variable was the mortality of weaver ants. The research results showed that the combination of 0.4 ml of paraffin oil with 0.6 ml of permethrin insecticide was the most effective in causing mortality of weaver ant pests and in reducing the dosage of synthetic insecticides.